Factors Affecting the Mental Health of Thai Medical Staff during the Second and Third Waves of the COVID-19 Pandemic: An Online Cross-sectional Survey - Anupansupsai, Rungarun; Saisavoey, Nattha; Supavekin, Suroj; Ratta-apha, Woraphat; Lortrakul, Juthawadee; Hataiyusuk, Somboon (Siriraj Medical Journal, 2024)
Objective: This comparative study of the second and third waves of the COVID-19 pandemic aimed to: 1) examine the mental health status of hospital staff; 2) describe the associations among various factors that affect mental health; and 3) investigate the impact of COVID-19. Materials and Methods: Data were collected from Siriraj Hospital staff using online questionnaires including demographics, staff characteristics, health behavior, readiness to handle COVID-19; COVID-19 impact; and the Thai version of the Depression Anxiety Stress Scales–21 (DASS-21). Results: Depression, anxiety, and stress scores were significantly higher in the third wave. Living in a high-surveillance area, social distancing difficulties, health behaviors, and office work all impacted mental health in both waves. Demographics, infection exposure outside the hospital, awareness of social distancing, and readiness to work from home impacted only the second wave. Direct work with COVID-19 patients impacted only the third wave. The common stressors included living expenses, daily life changes, and disease prevention costs in both waves, with COVID-19 news having a greater impact in the third wave. Main daily life impacts were income, transportation, and disease prevention equipment in both waves, with food becoming more important in the third wave. Conclusion: Mental health should be prioritized especially in severe waves, focusing on staff at high risk of infection, experiencing social distancing challenges, daily life changes, and having health problems. Disease protection should also be emphasized early on.